POLITICAL DISCRIMINATION AGAINST WOMEN IN ABI MORGAN'S SUFFRAGETTE (2015) FILM: AS A FEMINISM RESEARCH - Tasya Tsania Anarki; Yulistiyanti Yulistiyanti (Dinamika Bahasa dan Budaya, 2023)
This study examines political discrimination against women in the 2015 film entitled Suffragette using Simone De Beauvoir's theory of feminism. The movie tells the story of British women fighting for their rights during the 20th century. The study's methodology, which used qualitative research techniques, was feminism-focused. In the book The Second Sex, the researcher applied Simone De Beauvoir's feminist theory. This study has three goals. The first is to identify the factors that contribute to political discrimination. Secondly, to learn how political prejudice is reflected, and thirdly, to learn how political discrimination is portrayed in suffragette movies. The researcher draws the conclusion that there are three factors contributing to the political discrimination in the movie: societal stigma, the main subject, and government policy. Political discrimination is depicted in the movie in five different contexts: the parliament, the job, the home, the prison, and women's opinions. Both internal and exterior effects of political discrimination are depicted in the movie. Keywords : Political Discrimination, Suffragette, Feminism, Maud Watts